La responsabilità ecologica - Gianluca Cuozzo (Rivista di Estetica, 2021)
This essay explores the concept of responsibility with respect to today’s ecological and pandemic crisis. A fundamental category is identified in the ‘strategic repentance’, i.e. the ability to reconsider previous decisions taken following environmental feedback resulting from one’s activities. The model of this careful and circumspect behavior can be traced back on the one hand to the animal kingdom, on the other hand to the artistic domain. Thus, the bat and Michelangelo the sculptor become masters of a new action scheme, which is based on feedback rings and on in-progress revision of previously adopted strategies.